New Value Chain Analysis and Income Distribution Measurement of Khanom La Products in Nakhon Si Thammarat Province - Booranawong, Thitima; Theerachun, Sanatcha; Sampim, Tatcha (Suan Dusit Graduate School Academic Journal, 2022)
This research aimed to analyze the new value chain and study the income distribution measurement of Khanom La products of community enterprise groups in Nakhon Si Thammarat Province. This research was participatory action research, where the population consisted of six community enterprise groups for Khanom La production in Nakhon Si Thammarat Province. The data was collected by using an interview questionnaire, including production process data, selling price, production cost, and other expenses. Such data, collected by interviewing entrepreneurs, was used to analyze the new value chain, income ratio, and value added. The community’s income was also collected to analyze the income distribution of the enterprise groups. The results showed that: 1) For the value chain of Khanom La production, there were six related stakeholders, from upstream to downstream, including manufacturers, people with primary product processing, people with end product processing, wholesalers, retailers, and customers. 2) From the analysis of the income ratio and value added of each product in the new value chain, the results showed that product processing could increase the value added of raw materials up to 76.46 times compared with the price of traditional Khanom La. For the income ratio of each stakeholder, manufacturers had the lowest ratio of income, while people with processing and wholesalers had the highest ratio. 3) The results of the income distribution measurement of six community enterprise groups showed that the income was distributed in Nakhon Si Thammarat of 3,962,990.61 Baht, or 96.05%, and outside the area of 62,751.58 Baht, or 3.88% of the total income distribution. The development of community products that satisfied the requirements and customer behavior could increase the value added to the products and upgrade the basic economy for the community.